The use of numerical models on service equipment noise prediction in heavyweight and lightweight timber buildings. Issue 1 (March 2019) - Caniato, Marco; Bettarello, Federica; Schmid, Chiara; Fausti, Patrizio
In modern constructions, service equipment is the most used and complex technology. Air and liquid flow inside piping or conduit provides conditioning, well-being and comfort within buildings. Nevertheless, fluid movements inject both structure-borne and airborne noise, causing annoyance on people living inside edifices. In order to avoid this issue, the model provided by ISO 12354-5 standard could be used. Unfortunately, the standard describes very well the process in order to calculate the resulting noise caused by air flow service equipment, but it does not offer clear definitions of parameters related to waste water installations. As a consequence, very few researches and studies are available at present because of the difficulty on initial data set and on interpretation of requested parameters. In this article, the ISO 12354-5 method for waste water pipe source is critically analysed, modified and then applied to real case studies. Considerations on coupling terms are proposed, discussed and used in the standard equations, calculating the theoretical values and providing possible solutions for all missing data; results demonstrate how the suggested modified models matched very well measurements outcomes.